Notch polymorphisms associated with sensitivity of noise induced hearing loss among Chinese textile factory workers - Enmin Ding; Jing Liu; Huanxi Shen; Wei Gong; Hengdong Zhang; Haiyan Song; Baoli Zhu (BMC, 2018)
Abstract Background Noise induced hearing loss (NIHL) is a polygenic disease involving both genetic and environmental factors, and is one of the most important occupational health hazards worldwide. To date, the influence of Notch1 variants on the risk to develop NIHL has not been illuminated. This study was conducted to explore the effects of Notch1 polymorphisms on individual susceptibility to NIHL. Methods A total of 2689 industrial workers from one textile factory in east China were recruited to participate in the current study. Venous blood was collected, basic clinical data was obtained by questionnaires and pure-tone audiometry (PTA) tests were conducted by specialist physicians. Next we performed genotyping of three selected SNPs (rs3124594, rs3124599 and rs3124603) in the Notch1 gene in 535 NIHL patients and 535 controls. Subsequently, the main effects of the genotypes and their interactions were evaluated. Results Our results revealed that individuals with a GG of rs3124594, TT of rs3124603 (OR = 4.70 and 1.59 respectively) and the haplotype AAC (rs3124594-rs3124599-rs3124603) (OR = 14.95) were associated with an increased risk of NIHL in our study cohort. Stratified analysis showed that an increased NIHL risk was found in individuals exposed to work related noise for ≤16 years that also had the rs3124594 GG or rs3124603 CT/TT genotype with an OR of 4.20 and 1.73 respectively. Multifactor dimensionality reduction analysis indicated that rs3124594, rs3124599 and rs3124603 interacted with each other and were related to an increased risk to develop NIHL (OR = 3.60). Conclusions The genetic polymorphisms rs3124594 and rs3124603 within the Notch1 gene are associated with an increased risk of NIHL in a Chinese population and could potentially be used as biomarkers for NIHL in noise exposed workers.